Observation of a highly directional γ-ray beam from ultrashort, ultraintense laser pulse interactions with solids - Norreys, P; Santala, M; Clark, E; Zepf, M; Watts, I; Beg, F; Krushelnick, K; Tatarakis, M; Dangor, A; Fang, X; Graham, P; McCanny, T; et al. (1999)
Novel measurements of electromagnetic radiation above 10 MeV are presented for ultra intense laser pulse interactions with solids. A bright, highly directional source of y rays was observed directly behind the target. The y rays were produced by bremsstrahlung radiation from energetic electrons generated during the interaction. They were measured using the photoneutron reaction [63Cu(γ,n)62Cu] in copper. The resulting activity was measured by coincidence counting the positron annihilation γ rays which were produced from the decay of 62Cu. New measurements of the bremsstrahlung radiation at 1019 W cm-2 are also presented. © 1999 American Institute of Physics.